2019
DOI: 10.1371/journal.pone.0212876
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene climatic changes promoted demographic expansion and population reconnection of a Neotropical savanna-adapted bird, Neothraupis fasciata (Aves: Thraupidae)

Abstract: We performed phylogeographic and genetic structure analyses of Neothraupis fasciata joined with species distribution modelling to evaluate whether: (1) the distribution of genetic variability shows a pattern expected by the isolation-by-distance model; (2) the influence of the Pleistocene climate changes on species distribution; and (3) climate/climatic stability (hypothesis of climatic stability) as a predictor of population genetic diversity. Based on two molecular datasets (ND2 and FIB-5), the isolation-by-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 71 publications
2
14
5
Order By: Relevance
“…Our results are in accordance with other studies that found evidence of retraction of South American open biomes during warmer interglacial periods, and expansion during cold and dry glacial periods (Bueno et al , Lima‐Rezende et al ). As consequence of this spatio‐temporal dynamic of suitable areas, it can be expected that individuals evolved in isolation under different climatic and ecological pressures, and action of the genetic drift, accumulating differences that can limit gene flow between these lineages at the limits of respectively suitable areas after niche and population expansions (Hewitt ).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in accordance with other studies that found evidence of retraction of South American open biomes during warmer interglacial periods, and expansion during cold and dry glacial periods (Bueno et al , Lima‐Rezende et al ). As consequence of this spatio‐temporal dynamic of suitable areas, it can be expected that individuals evolved in isolation under different climatic and ecological pressures, and action of the genetic drift, accumulating differences that can limit gene flow between these lineages at the limits of respectively suitable areas after niche and population expansions (Hewitt ).…”
Section: Discussionsupporting
confidence: 94%
“…Secondarily, the heterogeneous landscape along the dry diagonal may have being limiting gene flow among the genetic lineages after contact was re-established among them. Thus, our results are in agreement with other studies (Lima-Rezende et al 2019, Silva et al 2019 indicating that Pleistocene climatic oscillations have had a strong influence in the intraspecific divergence of dry diagonal avifauna. Our results reinforce the initial proposition of Pennington et al (2000), then stressed by others (Werneck et al 2012, Fouquet et al 2014, that the different biomes of the dry diagonal should be considered as independent units from the biogeographical point of view.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Phylogeographical studies on organisms inhabiting grasslands in the Neotropics are still in their infancy (Bates et al 2003, Masello et al 2011, Campagna et al 2012a, 2012b, Lopes et al 2018, Moura et al 2018, Norambuena et al 2018, Lima-Rezende et al 2019, Corbett et al 2020, Rocha et al 2020, Santana et al 2020, limiting our understanding of the potential historical scenarios that characterize these ecosystems as well as the potential processes shaping genetic diversity across taxa. Therefore, new information about the phylogeographical history of taxa that specialize in this type of habitat is crucial to understand the historical and geological processes that have shaped the biodiversity of this biome (Antonelli et al 2010, Brumfield 2012.…”
Section: Up-down Distribution -Hypothesismentioning
confidence: 99%